Pelatihan Inklusif Advokasi Kebijakan Hak-Hak Penyandang Disabilitas di Komunitas SOBAT Difabel - Ulfah Fatmala Rizky (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
This community service’s goal was to train the skills and capabilities of persons with disabilities and non-disabled persons to be able to fight for the protection and fulfillment of the rights of persons with disabilities through a policy advocacy process. This community service was carried out online using the Google Meet video conference application and the Mentimeter presentation application. The methods used in this community service activity were: first, the seminar method to explain the material. Second, exercise questions and discussion methods to deepen and confirm participants’ understanding. Third, a descriptive quantitative method using a questionnaire instrument to evaluate the implementation and outcomes of this community service activity.